PENGARUH CITRA MEREK, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN NPK NITROKU 161616 - A. Rozi; Purwati, Mulia Inda; Evrina; Mumin, Abdul (Fakultas Hukum dan Ekonomi Bisnis, 2023)
This research aims to examine the influence of Brand Image, Price Perception and Product Quality on Consumer Purchasing Decisions for NPK Nitroku 161616. The research method used is associative descriptive. The research sample consisted of 78 respondents who were involved using the census method. The collected data was analyzed using multiple linear regression analysis. The research results show that Brand Image, Price Perception, and Product Quality significantly influence Consumer Purchasing Decisions for NPK Nitroku 161616. Brand Image has a significant positive influence, meaning that the more positive the brand image of NPK Nitroku 161616, the higher the consumer's tendency to buy. that product. Price Perception also has a significant positive influence, indicating that the more affordable the product is, the more likely consumers are to buy it. Apart from that, Product Quality also has a significant positive influence on Consumer Purchasing Decisions, which indicates that the higher the product quality perceived by consumers, the more likely they are to buy NPK Nitroku 161616. This research provides important implications for NPK Nitroku 161616 in designing marketing strategy. Increasing a positive brand image, offering affordable prices, and improving product quality can be factors that support consumer purchasing decisions. In the face of increasingly fierce competition in the market, companies need to pay attention to these aspects to gain a competitive advantage and maintain existing market share.